Halofuginone, a promising drug for treatment of pulmonary hypertension. (31st July 2021) - Jain, Pritesh P.; Zhao, Tengteng; Xiong, Mingmei; Song, Shanshan; Lai, Ning; Zheng, Qiuyu; Chen, Jiyuan; Carr, Shane G.; Babicheva, Aleksandra; Izadi, Amin; Rodriguez, Marisela; Rahimi, Shamin; et al.
Abstract : Background and Purpose: Halofuginone is a febrifugine derivative originally isolated from Chinese traditional herb Chang Shan that exhibits anti‐hypertrophic, anti‐fibrotic and anti‐proliferative effects. We sought to investigate whether halofuginone induced pulmonary vasodilation and attenuates chronic hypoxia‐induced pulmonary hypertension (HPH). Experimental Approach: Patch‐clamp experiments were conducted to examine the activity of voltage‐dependent Ca 2+ channels (VDCCs) in pulmonary artery smooth muscle cells (PASMCs). Digital fluorescence microscopy was used to measure intracellular Ca 2+ concentration in PASMCs. Isolated perfused and ventilated mouse lungs were used to measure pulmonary artery pressure (PAP). Mice exposed to hypoxia (10% O2 ) for 4 weeks were used as model of HPH for in vivo experiments. Key Results: Halofuginone increased voltage‐gated K + (Kv ) currents in PASMCs and K + currents through KCNA5 channels in HEK cells transfected with KCNA5 gene. HF (0.03–1 μM) inhibited receptor‐operated Ca 2+ entry in HEK cells transfected with calcium‐sensing receptor gene and attenuated store‐operated Ca 2+ entry in PASMCs. Acute (3–5 min) intrapulmonary application of halofuginone significantly and reversibly inhibited alveolar hypoxia‐induced pulmonary vasoconstriction dose‐dependently (0.1–10 μM). Intraperitoneal administration of halofuginone (0.3 mg·kg −1, for 2 weeks) partly reversed established PH in mice. Conclusion and Implications: Halofuginone is a potent pulmonary vasodilator by activating Kv channels and blocking VDCC and receptor‐operated and store‐operated Ca 2+ channels in PASMCs. The therapeutic effect of halofuginone on experimental PH is probably due to combination of its vasodilator effects, via inhibition of excitation–contraction coupling and anti‐proliferative effects, via inhibition of the PI3K/Akt/mTOR signalling pathway.